The Tunisian stance on the Italian occupation of Libya in 1911 - Boutaibi, Mohamed; Rebai, Djemaa (The journal of research and scientific studies, 2026)
Keywords: Invasion italienne -- Libye

Libia 1922-1931: le operazioni militari italiane - Saini Fasanotti, Federica (Stato maggiore dell'esercito, Ufficio storico, 2012)
Keywords: Djebel Nefousa -- 1912-1951; Invasion italienne -- Libye; Italie -- colonies

Not a Happy History — Italy & Libya - Wright, John (The Maghreb Review, 2022)
Italy “ruled” Libya for 32 years (1911–43), and both still largely resent the experience. Italy, “the least of the Great Powers”, lacked the necessary capacity and experience to conquer and rule foreign colonies, particularly one as poor and unpromising as Turkish North Africa — the “Crate of Sand”. And Libyans, far from welcoming Italians as “liberators from Turkish oppression” defended their own for years of violent “anti-colonial struggle”, and particularly against Italian fascist ideology. Episodes and personalities from that conflict have since been appropriated by successive Libyan regimes to enhance their own historical legitimacy and contemporary credibility, while some modern Italian historians have also manipulated Italo-Libyan historical memories. Italy’s passive acceptance of the resultant historical “guilt” seems partly intended to ensure continuing access to Libyan resources, as well as better management of the flow of African migrants across the central Mediterranean.
Keywords: Invasion italienne -- Libye

Conquering Libya (1911–1932): A Crusade? - Cresti, Federico (The Maghreb Review, 2022)
When the Italian government decided to conquer Libya, the military expeditionary force was instructed to avoid any action that could be interpreted as an affront to the religion of the population. However, in the course of military operations, several Muslim religious buildings were damaged or destroyed and Ottoman propaganda presented the aggression as a Christian attack on Islam. The resistance against the occupation soon took on the characteristics of holy war, its main leaders raising the banner of the jihād.
Keywords: Invasion italienne -- Libye

‏خليفة بن عسكر: قائد الجهادين - العزابى, مسعود عيسى (الفسيفساء, 2022)
Keywords: Biographies -- Djebel Nefousa -- 20e siècle; Invasion italienne -- Libye

موقف الاتحاد بين الاترك من الغزو الايطالي لليبيا - ابراهيم, فادية عبد العزيز (سلسلة الدراسات التاريخية, 2006)
Keywords: Invasion italienne -- Libye

جهاد الليبيين ضد الغزو الإيطالي من خلال الوثائق الإنجليزية: أحمد الشريف، رمضان السويحلي، 1911-1920 - السويحلي, صلاح الدين عوض (ملامح الجهاد الليبي, 2008)
Keywords: Invasion italienne -- Libye; Sources

Les Ibadites du Djebel Nefousa dans la vision coloniale italienne. Les débuts de la "question berbère" en Libye (1911-1913) - Cresti, Federico (Minorités en Méditerranée au XIXe siècle: identités, identifications, circulations, 2019)
Présentation de l'éditeur : "La Méditerranée du XIXe siècle constitue un terrain particulièrement fécond pour une analyse des multiples dynamiques de la construction des minorités. Cet ouvrage interroge les modalités de la fixation des identités par les États impériaux et par les minorités elles-mêmes. Il accorde une attention particulière à l’articulation entre les critères religieux, linguistiques, nationaux et territoriaux dans la catégorisation de ces identités collectives et individuelles. Il apporte un éclairage sur la mise en place de nouveaux modes d’administration des minorités, montrant les circulations et les transferts des normes et des pratiques, entre minorités au sein d’un même empire, mais aussi d’un empire à l’autre."
Keywords: Djebel Nefousa -- 1912-1951; Ibadisme -- Djebel Nefousa; Invasion italienne -- Libye

The Italian invasion of Libya in 1911 and the nineteen years of Libyan resistance - Bugaighis, Saad (University of Washington, 2011)
Keywords: Invasion italienne -- Libye

L'occupation italienne de la Libye: les préliminaires, 1882-1911 - Larfaoui, Mahmoud-Hamdane (Histoire et perspectives Méditerranéennes, 2010)
Keywords: Invasion italienne -- Libye

The Anti-Colonial Empire: Ottoman Mobilization and Resistance in the Italo-Turkish War, 1911-1912 - McCollum, Jonathan (University of California, 2018)
The Italo-Turkish War (1911-1912), now remembered primarily as Italy’s war for what is now Libya, swelled from a localized colonial invasion into a significant Mediterranean conflict and a global cause cï¿½lï¿½bre that attracted support and aid for the embattled Ottoman regime from diverse locations both inside and outside the borders of the empire. This dissertation examines the means by which the Ottoman Empire erected an asymmetric defense of its last North African provinces to preserve its territory and empire from Italian occupation and annexation. Drawing on sources in Ottoman Turkish, Arabic, Greek, and Judeo-Spanish, this study demonstrates how the Sublime Porte and the Committee of Union and Progress (CUP) initially deployed a rhetoric of unity, constitutionalism, and international law to protect the empire from the Italian invasion. Due to the efficacy of Italian diplomacy, the Ottomans, unable to enlist Great Power support for the preservation of imperial territory, developed a defensive strategy for its North African territories that relied primarily on humanitarianism and volunteerism. This dissertation, therefore, investigates the vital contribution of pan-Islamism and the broad appeal of a loose ideology of Muslim anticolonialism in the empire’s attempts to bolster its forces with international aid and volunteers. While many studies tend to brush aside the importance of early twentieth-century pan-Islamism as either a pipe dream of Wilhelmine champions of German imperialism and their Ottoman collaborators or as merely a rhetorical movement devoid of substantial consequence, this dissertation reveals how global appeals to Islamic unity to combat European expansionism translated into material benefits for Ottomans on the battlefield. Through an examination of documents from the Turkish Red Crescent and the Turkish General Staff archives, it highlights the crucial assistance of global Islamic humanitarian aid to the Ottoman war effort in the form of sizeable financial contributions to the Ottoman Red Crescent from Muslims over the duration of the conflict. The Red Crescent organization provided a means to funnel aid to the battlefield collected in mosques, mass meetings, newspaper subscriptions, and Islamic associations within and without the Ottoman Empire. This charitable aid facilitated the deployment to North Africa of multiple Red Crescent teams which assumed, in most cases, sole responsibility for the medical care of both soldiers and civilians of the Ottoman provinces. Simultaneously, the Ottoman ranks in Tripolitania and Cyrenaica swelled as calls for coreligionist volunteers to take up arms were heeded throughout Africa and Asia. Ultimately, the empire’s anticolonial ideology proved an effective unifier for the many Muslims around the world who shouldered a great deal of the cost of the conflict. While Italy’s expenses for its war for colonial expansion ballooned, the defense of North Africa cost the Ottoman treasury very little.
Keywords: Invasion italienne -- Libye

Gli studi italiani sul colonialismo italiano in Libia - Labanca, Nicola (Un colonialismo: due sponde del Mediterraneo: atti del Seminario di studi storici italo-libici, Siena-Pistoia, 13-14 gennaio 2000, 2000)
Keywords: Invasion italienne -- Libye

La guerra italiana per la Libia: 1911-1931 - Labanca, Nicola (Biblioteca storica, 2012)
Keywords: Invasion italienne -- Libye

Le operazioni militari in Libia e nel Sahara 1914-1918 - Rosselli, Alberto (2007)
Keywords: Invasion italienne -- Libye

Giolitti e San Giuliano di fronte alla questione della chiusura dell’impresa di Libia: annessione o protettorato? - Ferraioli, Gian Paolo (Africa: Rivista trimestrale di studi e documentazione dell’Istituto italiano per l’Africa e l’Oriente, 2001)
La décision prise par le gouvernement italien, en octobre 1911, de ne pas donner le status de protectorat à la Libye constitua une des principales causes de la transformation de la guerre italo-turque en une guérilla longue et tragique entre les Arabes de Libye et les Italiens. En effet, le choix de Giolitti d'annexer directement la Libye au Royaume d'Italie poussa les Arabes à se joindre aux Turcs pour combattre contre le commun ennemi "chrétien". Pourquoi donc l'Italie rejecta-t-elle la formule du protectorat, si cette formule pouvait prévenir un tel danger? Cet article cherche à répondre à cette question, en analysant surtout la politique clairvoyante du ministre des Affaires étrangères du quatrième gouvernement Giolitti, le marquis Antonino di San Giuliano, qui fut réellement sur le point de mettre fin à la question de Libye avec un protectorat.
Keywords: Invasion italienne -- Libye

The Anglo-Sanusi war (1915-1916) - Bernini, Simone (The Maghreb Review, 2001)
Keywords: Invasion italienne -- Libye

Une lettre adressée par Ghouma al-Mahmoudi au Consul d’Angleterre à Tunis - Bouzid, Lamjed (Revue d'histoire Maghrébine, 2002)
Keywords: Invasion italienne -- Libye

Réveiller l'archive d'une guerre coloniale: photographies et écrits de Gaston Chérau, correspondant de guerre lors du conflit italo-turc pour la Libye (1911-1912) - Chérau, Gaston (Creaphiseditions, 2018)
Keywords: Invasion italienne -- Libye

Nazionalismo e collaborazionismo in Libia: i colloqui di Tripoli (novembre 1912) - Bernini, Simone (Journal of Libyan Studies, 2000)
Keywords: Invasion italienne -- Libye

Notabili libici e funzionari italiani: l'amministrazione coloniale in Tripolitania (1912-1919) - Berhe, Simona (Stato, esercito e controllo del territorio, 2015)
Keywords: Invasion italienne -- Libye